Mulla Sadra, The Elixir of the Gnostics - Atif Khalil (International Institute of Islamic Thought, 2004)
Professor Chittick undertook the translation from Arabic of the Iksir al- `Arifin (Elixir of the Gnostics) at the bequest of the Sadra Islamic Philosophy Research Institute. No doubt, one of the institute’s reasons for making this request is because Chittick is currently one of North America’s most formidable scholars of the Islamic “sapiental” tradition, the stream of thought that combined both falsafah (philosophy) and tasawwuf (Sufism). He has to his credit some of the best English translations of medieval Arabic and Persian texts. Chittick’s wealth of knowledge comes out in the extensive endnotes, running 28 pages, which not only help explain obscure passages and terms, but also trace many of the ideas to their sources. The Elixir is a unique work of Sadra’s in that it is, as Chittick notes in the introduction, something of a translation of Kashani’s (d. 1213-14) Persian Jawidan-nama (Book of the Everlasting). One could argue that the Everlasting serves simply as a template for Sadra’s work, since he removes 40 percent of the text and increases it by half the length of the original. In that regard, most of the Elixir is original. However, the basic structure of the Everlasting, four parts divided into 35 chapters, remains. The four parts deal with the classification of the various sciences, the nature of the soul, and cosmic beginnings and ends. Within the rubric of these four broad categories, a range of subjects are covered: from time, space, Adam, and Satan, to birth, death, and the resurrection. The Everlasting, it is worth noting, was also translated into English by Chittick just 2 years before the publishing of this work, in the Heart of Islamic Philosophy (pp. 194-233), another factor rendering him a most suitable translator for this text ...